Establishing a Porcine Model of Small for Size Syndrome following Liver Resection - Mohammad Golriz; Maryam Ashrafi; Elias Khajeh; Ali Majlesara; Christa Flechtenmacher; Arianeb Mehrabi (Canadian Journal of Gastroenterology and Hepatology)
Background. Small for size syndrome (SFSS) is responsible for a high proportion of mortalities and morbidities following extended liver resection. Aim. The aim of this study was to establish a porcine model of SFSS. Methods. Twenty-four Landrace pigs underwent liver resection with a remnant liver volume of 50% (group A, n=8), 25% (group B, n=8), and 15% (group C, n=8). After resection, the animals were followed up for 8 days and clinical, laboratory, and histopathological outcomes were evaluated. Results. The survival rate was significantly lower in group C compared with the other groups (p<0.001). The international normalized ratio, bilirubin, aspartate transaminase, alanine transaminase, and alkaline phosphatase levels increased shortly after surgery in groups B and C, but no change was observed in group A (p<0.05 for all analyses). The histopathological findings in group A were mainly mild mitoses, in group B severe mitoses and hepatocyte ballooning, moderate congestion, and hemorrhage, along with mild necrosis, and in group C extended tissue damage with severe necrosis, hemorrhage, and congestion. Conclusions. Combination of clinical, laboratory, and histopathological evaluations is needed to confirm the diagnosis of SFSS. 75% liver resection in porcine model results in SFSS. 85% liver resection causes irreversible liver failure.